1999
DOI: 10.1038/sj.bjp.0702500
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between group IIA‐phospholipase A2 and inducible NO‐synthase in rat renal mesangial cells

Abstract: 1 Features of glomerulonephritis are expression of the inducible form of NO synthase (iNOS) as well as expression of the secretory group IIA-phospholipase A 2 (sPLA 2 ) in mesangial cells. Interleukin 1b (IL-1b) induces both enzymes with a similar time course resulting in an increase in nitrite production and sPLA 2 -IIA activity. In this study we investigated the relationship between the formation of NO and sPLA 2 -IIA induction in rat renal mesangial cells. 2 Incubation of mesangial cells with the NO-donor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…Recently, we have obtained evidence that group IIA sPLA 2 gene expression in mesangial cells is strongly dependent on NO formation by iNOS (Rupprecht et al, 1999). Similarly, Cox-2 mRNA expression and enzyme activity are stimulated by NO in mesangial cells (Salvemini, 1997).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Recently, we have obtained evidence that group IIA sPLA 2 gene expression in mesangial cells is strongly dependent on NO formation by iNOS (Rupprecht et al, 1999). Similarly, Cox-2 mRNA expression and enzyme activity are stimulated by NO in mesangial cells (Salvemini, 1997).…”
Section: Discussionmentioning
confidence: 94%
“…Recently we described that the IL1b-stimulated gene expression of group IIA sPLA 2 is strongly dependent on NO produced by iNOS in mesangial cells (Rupprecht et al, 1999). Since group IIA sPLA 2 and Cox-2 were inhibited at the transcriptional level by CGP-43182, we hypothesized that the induction of iNOS in mesangial cells might also be aected by this compound.…”
Section: Eect Of Cgp-43182 On Inos Induction and Nitrite Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that sPLA 2 enhances the response of leukocytes to LPS, which suggests a direct interaction of sPLA 2 with LPS (34). Rupprecht et al have shown and suggested cross talk between sPLA 2 and iNOS in rat renal mesangial cells (35). Recently, Tsukahara et al reported that the PLA 2 inhibitor quinacrine inhibited iNOS expression in alveolar macrophages and reduced lung injury in acute pancreatitis.…”
Section: Discussionmentioning
confidence: 98%